Allergenicity of peanut allergens and its dependence on the structure. Issue 2 (9th January 2023) - Geng, Qin; Zhang, Ying; Song, Min; Zhou, Xiaoya; Tang, Yu; Wu, Zhihua; Chen, Hongbing
Abstract: Food allergies are a global food safety problem. Peanut allergies are common due, in part, to their popular utilization in the food industry. Peanut allergy is typically an immunoglobulin E‐mediated reaction, and peanuts contain 17 allergens belonging to different families in peanut. In this review, we first introduce the mechanisms and management of peanut allergy, followed by the basic structures of associated allergens. Subsequently, we summarize methods of epitope localization for peanut allergens. These methods can be instrumental in speeding up the discovery of allergenicity‐dependent structures. Many attempts have been made to decrease the allergenicity of peanuts. The structures of hypoallergens, which are manufactured during processing, were analyzed to strengthen the desensitization process and allergen immunotherapy. The identification of conformational epitopes is the bottleneck in both peanut and food allergies. Further, the identification and modification of such epitopes will lead to improved strategies for managing and preventing peanut allergy. Combining traditional wet chemistry research with structure simulation studies will help in the epitopes' localization.